Human dignity and contemporary liberalism - Stetson, Brad (Praeger, 1998)
This critique of the theory and practice of contemporary liberalism argues that a corrupted understanding of human dignity prevails on contemporary American life and, as a result, the country's civic and political practice is riddled with confusion and frustration.